2009
DOI: 10.1093/hmg/ddp231
|View full text |Cite
|
Sign up to set email alerts
|

Risk for nicotine dependence and lung cancer is conferred by mRNA expression levels and amino acid change in CHRNA5

Abstract: Nicotine dependence risk and lung cancer risk are associated with variants in a region of chromosome 15 encompassing genes encoding the nicotinic receptor subunits CHRNA5, CHRNA3 and CHRNB4. To identify potential biological mechanisms that underlie this risk, we tested for cis-acting eQTLs for CHRNA5, CHRNA3 and CHRNB4 in human brain. Using gene expression and disease association studies, we provide evidence that both nicotine-dependence risk and lung cancer risk are influenced by functional variation in CHRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
206
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(230 citation statements)
references
References 50 publications
18
206
4
1
Order By: Relevance
“…The primary psychiatric diagnoses in this sample were schizophrenia or schizoaffective disorder, substance dependence, and anxiety and depressive disorders; all of these conditions are known to be associated with increased rates of smoking (4,30,33). Previous studies suggest that 398Asn itself is not overrepresented in at least two studies of psychiatric populations (36,37). It is also not overrepresented in our sample (psychiatric illness vs. genotype, n = 309; χ 2 = 0.92, P = 0.630).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…The primary psychiatric diagnoses in this sample were schizophrenia or schizoaffective disorder, substance dependence, and anxiety and depressive disorders; all of these conditions are known to be associated with increased rates of smoking (4,30,33). Previous studies suggest that 398Asn itself is not overrepresented in at least two studies of psychiatric populations (36,37). It is also not overrepresented in our sample (psychiatric illness vs. genotype, n = 309; χ 2 = 0.92, P = 0.630).…”
Section: Resultsmentioning
confidence: 74%
“…The unique finding here is that psychiatric illnesses affect the same circuit independently from and in addition to the α5 genetic effect. 398Asn has repeatedly shown a signal for smoking (5,7,37,(50)(51)(52)(53)(54) but, thus far, not for increased smoking in other psychiatric diagnoses (36,37). Because the sample sizes for psychiatric diagnoses in the present and many of these previous samples are relatively small, these disorders might potentially show a signal with still larger sample sizes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The strong correlation between genetic variants in CHRNA5‐CHRNA3‐CHRNB4 , here represented by rs1051730, and CPD suggests that the minor allele (T) could be associated with reduced sensitivity to plasma nicotine levels, leading to increased tobacco consumption 23. Smokers homozygous for the minor allele inhale more often than noncarriers and heterozygous smokers 7.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, genome-wide association studies have identified that polymorphisms in nAChR genes in gene clusters for other subunits, ␣5/␣3/␤4 and ␣6/␤3, are associated with tobacco addiction (Thorgeirsson et al, 2008;Saccone et al, 2009;Bierut, 2010). Allelic variation and expression levels of ␣5 subunits have been particularly strongly associated, across independent studies Wang et al, 2009;Bierut, 2010). The ␣5 subunits, like ␤3 subunits, are accessory subunits that are known to modify the properties of ␣4-or ␣6-containing nAChRs respectively (Tumkosit et al, 2006;Grady et al, 2010;Kuryatov et al, 2011), but the roles of ␣5-containing (␣5*) or ␤3* nAChRs in normal brain function and in nicotine action in situ are poorly understood.…”
Section: Introductionmentioning
confidence: 99%